A case report and analysis on the application of holographic meridian scraping therapy in a patient with refractory hypertension (全息经络刮痧疗法治疗难治性高血压1例的护理体会) - LIANG Mengnv (梁孟女); JI Yunfei (吉云飞); SONG Libo (宋丽波); ZHAO Nan (赵楠); LI Jing (李静); LIU Huaoing (刘焕萍) (中西医结合护理, 2021)
This paper summarized the nursing experience of holographic meridian scraping in a patient with refractory hypertension. A comprehensive evaluation based on Traditional Chinese Medicine diagnosis of face, hand and tongue inspection and scraping should be carried out before implementation of holographic meridian scraping therapy. Therapeutic principles and scraping area should be determined before nursing management based on syndrome differentiation, and a standard scraping procedure is required to control blood pressure and improve the symptoms. (本文总结全息经络刮痧治疗1例难治性高血压患者的护理经验。实施中医全息经络刮痧前应结合面诊、手诊、舌诊及刮痧诊断进行综合中医护理评估, 辨证施护, 刮痧治疗期间要确定好治疗原则、刮痧部位, 规范操作方法, 进而达到辅助降压、改善症状的目的。)